Analysis of The Influence of Free Shipping, Cash on Delivery, and Live Streaming on Purchase Decisions at Tiktok Shop in Surabaya City - Utomo, Priyo (International Business Management - Universitas Ciputra, 2023)
TikTok shop is an online shopping service feature of the TikTok application with the problem of late receipts being the focus of research. The objectives of this research was to find out what kind of impact cash-on-delivery transactions have and live streaming on purchasing decisions at the online store TikTok shop for people in the city of Surabaya partially and simultaneously. This type of research uses descriptive research methods with a quantitative approach with a population of 200 respondents in the Surabaya City community. With data collection techniques using questionnaires, data analysis in this study was multiple linear regression and data processing using SPSS software. The results of the research conducted, it shows that Cash on delivery (X1) has a positive and partially significant effect because t count > t table and sig <0, 05 with a result of 5.429 > 1.652 and a significance value of 0.000 <0.05. Live streaming (X2) has a positive and partially significant effect because t count > t table and sig <0.05 with the result 10.225 > 1.652 and the significance value is 0.000 <0.05. And simultaneously cash on delivery (X1), and live streaming (X2) has a positive and significant effect on purchasing decisions (Y) with the results f count> f table 101.259> 2.65 significant value of f test 0.000 <0.05